2020
DOI: 10.1002/adfm.202003302
|View full text |Cite
|
Sign up to set email alerts
|

Electric‐Field‐Assisted Growth of Vertical Graphene Arrays and the Application in Thermal Interface Materials

Abstract: Owing to the development of electronic devices moving toward high power density, miniaturization, and multifunction, research on thermal interface materials (TIMs) is become increasingly significant. Graphene is regarded as the most promising thermal management material owing to its ultrahigh in-plane thermal conductivity. However, the fabrication of high-quality vertical graphene (VG) arrays and their utilization in TIMs still remains a big challenge. In this study, a rational approach is developed for growin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
99
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 115 publications
(99 citation statements)
references
References 52 publications
0
99
0
Order By: Relevance
“…Top-down graphene nanoflakes [114] 10 ----rGO/epoxy composite [20] 2.65 ----VAGF [21] 614.86 -86.023 2.255 -GF/E-40 [23] 384.9 -910. 77 12.33 -AGAs [25] 6.57 -20/150 -GHF-2800 [24] 35.5 -406 --HLGP [16] 143 5.8-22.5 -0.87 -Bottom-up VG arrays [12] 53.5 11.8 ---VG [17] 680 ----…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Top-down graphene nanoflakes [114] 10 ----rGO/epoxy composite [20] 2.65 ----VAGF [21] 614.86 -86.023 2.255 -GF/E-40 [23] 384.9 -910. 77 12.33 -AGAs [25] 6.57 -20/150 -GHF-2800 [24] 35.5 -406 --HLGP [16] 143 5.8-22.5 -0.87 -Bottom-up VG arrays [12] 53.5 11.8 ---VG [17] 680 ----…”
Section: Resultsmentioning
confidence: 99%
“…built-in electric field into the reaction system. [12] Moreover, they also found that the growth rate of VG increased with the electric field intensity.…”
Section: Morphology and Growth Rate Of Vg In Pecvdmentioning
confidence: 96%
See 3 more Smart Citations